Synods of Bishops of the Pope Benedict XVI - ROZKRUT, TOMASZ (Prawo Kanoniczne, 2013)
An important institution of the post-conciliar Church, and - as we can even say – a sign of his life and dynamism, and first of all, concern of common good, is relatively young and lively institution of the Synod of Bishops. It was called into existence during the period of the Second Vatican Council by the Pope Paul VI (1963-1978), largely as a response to the suggestions in the perspective of aggiornamento. The institution of the Synod of Bishops became particularly lively during a long pontificate of the Pope John Paul II (1978-2005) who chaired its 15 meetings and announced the Synod of Bishops concerning the Eucharist that took place during the pontificate of the Pole Benedict XVI. Also, the Pope Benedict XVI (2005-2013) regularly called the Synod of Bishops maintaining a creative influence of the Bishop of Rome on functioning of the contemporary universal Church this way. Synods of Bishops that took place during the pontificate of the Pope Benedict XVI are undoubtedly the reflection of this pontificate; in particular they helped the Bishop of Rome to take a look, in the light of the universality of the Church, at the current significant problems as well as develop new directions of pastoral actions.